2007
DOI: 10.1186/1471-2342-7-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and qualitative differences in subcutaneous adipose tissue stores across lipodystrophy types shown by magnetic resonance imaging

Abstract: Background: Lipodystrophies are characterized by redistributed subcutaneous fat stores. We previously quantified subcutaneous fat by magnetic resonance imaging (MRI) in the legs of two patients with familial partial lipodystrophy subtypes 2 and 3 (FPLD2 and FPLD3, respectively). We now extend the MRI analysis across the whole body of patients with different forms of lipodystrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…Nevertheless, high blood leptin levels are associated with infertility in PCOS (40), in which the correlation between leptin, insulin, and visceral fat is lost (41). This divergence in leptin levels between infertile PCOS and FPLD could be attributed to not only fat mass but also fat repartition: it has been recently shown that fat is globally distributed in PCOS, whereas it is supraclavicular and abdominovisceral in FPLD (42,43). The pregnancies of the four LMNA-mutated women reported here (five pregnancies, with two miscarriages for the same woman) were all achieved, with the patients taking insulin sensitizers (metformin in four cases, rosiglitazone in one case).…”
Section: Discussionmentioning
confidence: 94%
“…Nevertheless, high blood leptin levels are associated with infertility in PCOS (40), in which the correlation between leptin, insulin, and visceral fat is lost (41). This divergence in leptin levels between infertile PCOS and FPLD could be attributed to not only fat mass but also fat repartition: it has been recently shown that fat is globally distributed in PCOS, whereas it is supraclavicular and abdominovisceral in FPLD (42,43). The pregnancies of the four LMNA-mutated women reported here (five pregnancies, with two miscarriages for the same woman) were all achieved, with the patients taking insulin sensitizers (metformin in four cases, rosiglitazone in one case).…”
Section: Discussionmentioning
confidence: 94%
“…We have previously sequenced LMNA exon 11 in DNA from 194 Creole subjects with African ancestry from the Reunion Island (29), and we did not find the p.T655fsX49 mutation. (42), shows that sc lipoatrophy is absent or markedly less severe in patients with LMNA non-codon 482-associated mutations than in those with codon 482-associated mutations. In addition, MRI showed a fatty degeneration of glutei and adductor muscles in patient 1.…”
Section: Molecular Studiesmentioning
confidence: 96%
“…We have developed a standardized methodology for semiautomated quantitation of subcutaneous adipose stores from MRI to study differences between subjects with lipodystrophy (88,89). Inspection of whole body magnetic resonance images, and also regional and segmental scans, showed remarkable differences between different types of lipodystrophy (Fig.…”
Section: Phenomic Studies Of Fat Distribution Using Magnetic Resonancmentioning
confidence: 99%